1993
DOI: 10.1063/1.108522
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tm3+ blue emission in Tm, Yb, co-doped fluorophosphate glasses due to back energy transfer processes

Abstract: Up-conversion emission spectra of fluorophosphate glasses doped with Tm3+ and co-doped with Tm3+ and Yb3+ ions were obtained under two different excitation wavelengths (657 and 683 nm). Both samples show a stronger emission centered at 450 nm than the ones centered at 478 and 363 nm when 3F2 level of Tm3+ is excited at 657 nm. If 3F3 level of Tm3+ is excited with the 683 nm light the 478 nm emission of the double doped sample becomes much stronger (about 200 times) than the same emission of the single doped sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Therefore, the blue up-conversion emissions corresponding to 1 D 2 e 3 F 4 and 1 I 6 e 3 H 4 transitions are weakened. The population of 3 F 4 level is affected by the following processes as Yb 3þ ion exist: ① The back energy transfer process: 2 F 5/2 (Yb 3þ ion) e 3 H 5 (Tm 3þ ion) increases the 3 H 5 level population, and then increases the 3 F 4 level population by the nonradiative relaxation from 3 H 5 level to 3 F 4 level [33]; ② The 3 F 4 population decreases for the cross relaxations: 1 D 2 e 3 F 4~3 H 4 e 1 I 6 and 3 H 4 e 3 F 4~3 H 6 e 3 F 4 are weakened by energy transfer from Tm 3þ ion to Yb 3þ ion. In general, the population of 3 F 4 level is less sensitive to Yb 3þ ion concentration compared to that of 3 H 4 level.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the blue up-conversion emissions corresponding to 1 D 2 e 3 F 4 and 1 I 6 e 3 H 4 transitions are weakened. The population of 3 F 4 level is affected by the following processes as Yb 3þ ion exist: ① The back energy transfer process: 2 F 5/2 (Yb 3þ ion) e 3 H 5 (Tm 3þ ion) increases the 3 H 5 level population, and then increases the 3 F 4 level population by the nonradiative relaxation from 3 H 5 level to 3 F 4 level [33]; ② The 3 F 4 population decreases for the cross relaxations: 1 D 2 e 3 F 4~3 H 4 e 1 I 6 and 3 H 4 e 3 F 4~3 H 6 e 3 F 4 are weakened by energy transfer from Tm 3þ ion to Yb 3þ ion. In general, the population of 3 F 4 level is less sensitive to Yb 3þ ion concentration compared to that of 3 H 4 level.…”
Section: Resultsmentioning
confidence: 99%
“…The Judd-Ofelt analysis has been carried out and it is concluded that glasses containing NaF have stronger optical intensities. The upconversion emission of Tm 3+ /Yb 3+ ions co-doped fluorophosphate glasses is also investigated and a strong emission line at 480 nm is observed [77]. It is concluded that the addition of Yb 3+ ions to the singly doped Tm 3+ glasses increases the upconversion intensity up to 200 times.…”
Section: Summary Of the Ongoing Researchmentioning
confidence: 94%
“…26 The Yb 3+ ion can also transfer energy to other lanthanide ions, such as Ho 3+ ions, 50 Er 3+ ions, 51 and Tm 3+ ions. 52 Furthermore, the NIR emission band (around 980 nm) of Yb-Tip-MSS under the visible excitation is located in the biological transparent window (700-1000 nm), 9 and the emissive (around 1000 nm, see Fig. S6 †) protein conjugate has been applied in medical diagnostics.…”
Section: Photoluminescence Studiesmentioning
confidence: 99%